585 The Relationship between Napping and Behavioral Problems among Vocational High School Students in China. (3rd May 2021) - Han, Jing; Huang, Rendong; Yue, Lei; Cui, Naixue; Cao, Fenglin
Abstract: Introduction: Although napping is very common and related to the outcome of individual development, the relationship between napping and health is not the same in different social and cultural contexts. In China, napping is considered as a healthy lifestyle and is often associated with better adolescent development outcomes. As a special group of teenagers (the academic level does not meet the requirements of ordinary high school), vocational high school students have a higher incidence of behavioral problems than ordinary high school students. Therefore, the purpose of this study is to explore the characteristics of napping and its relationship with behavioral problems in vocational high school students. Methods: The napping questionnaire, Youth Self Report (YSR), general information questionnaire and other tools for covariates were used to measure 2505 high school students (62.04% boys, 37.96% girls, 16.71±0.02 years), recruited by convenient sampling. The relationship between nappingand behavioral problems was analyzed by multiple linear regression. Results: 72.58% of the participants reported taking a midday nap at least three days per week during the past month, and 55.79% of our sample reported naps more than 30 minutes. Multiple regression analysis showed that nap frequency was negatively associated with high school students' behavior problems after controlling for general characteristics and other important covariates. Compared with high school students who did not nap or napped less than 1 time/week, high school students who napped 1–2 times/week or 3–4 times/week had lower level of both internalizing behavior problems and externalizing behavior problems. There was no statistically significant association between nap duration and behavior problems. Conclusion: This study finds that when napping is allowed, moderate frequency of napping is associated with lower level of internalizing and externalizing behavioral problems in vocational high school students, while nap duration is not significantly associated with behavioral problems. Further research is needed to explore the mechanism of the relationship between napping and behavior problems. Support (if any):